2022
DOI: 10.1007/s10329-022-01022-z
|View full text |Cite
|
Sign up to set email alerts
|

Birth of a wild black howler monkey (Alouatta pigra) at an anthropogenic site

Abstract: We present the first description of a diurnal live birth of a wild black howler monkey (Alouatta pigra). The mother formed part of a group of five individuals inhabiting an anthropogenic setting in the tropical lowlands of southeast Mexico. A total of 7 h and 50 min passed from the rupture of the amniotic sac early in the day to the crowning of the infant from the birth canal. The delivery of the infant lasted ~ 3 min. We describe the event while referencing images and time points in a supplementary video reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The observed behaviours during the post-parturition phase of diurnal births in previous studies in Alouatta conformed with the reported events (Sekulic, 1982;Nisbett & Glander, 1996;Dias, 2005;Camarago & Ferrari, 2007;Peker et al 2009;Martins et al 2015;Cárdenas-Navarrete & Van Belle, 2023). These include cleaning of the neonate and self, delivery and consumption of the placenta, ingestion of the umbilical cord, and minimal interactions with other group members.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The observed behaviours during the post-parturition phase of diurnal births in previous studies in Alouatta conformed with the reported events (Sekulic, 1982;Nisbett & Glander, 1996;Dias, 2005;Camarago & Ferrari, 2007;Peker et al 2009;Martins et al 2015;Cárdenas-Navarrete & Van Belle, 2023). These include cleaning of the neonate and self, delivery and consumption of the placenta, ingestion of the umbilical cord, and minimal interactions with other group members.…”
supporting
confidence: 87%
“…The temporal and spatial flexibility that has been previously observed in members of the genus Alouatta is suggested to be attributed to their energetically conservative ecology, as they are known to engage in prolonged diurnal resting periods (Sekulic, 1982;Nisbett & Glader, 1996;Dias, 2005;Carmargo & Ferrari, 2007;Peker et al, 2009;Martins et al, 2015;Cárdenas-Navarrete & Van Belle, 2023). Potentially minimising the pressure for nocturnal births, allowing day-time parturitions to occur.…”
mentioning
confidence: 98%